Free hand. - Bickers, Charles (Far Eastern Economic Review, 2001)
The decision by Japan's Sharp Corporation to use the controversial open-source software Linux on its new Zaurus organizer is surprising. Linux is popular as an operating system for web servers, but is has yet to prove itself in the personal-computer market, where it is difficult to use and lacks quality software. However, according to Stacey Quandt, an analyst at a computer-research and consulting company, the coupling of Linux with the Java computer language could bring about acceptance.